Post-hepatectomy haemorrhage: a definition and grading by the International Study Group of Liver Surgery (ISGLS) - Rahbari, Nuh Nabi; Garden, O. James; Padbury, Robert; Maddern, Guy; Koch, Moritz; Hugh, Thomas J.; Fan, Sheung Tat; Nimura, Yuji; Figueras, Joan; Vauthey, Jean-Nicolas; Rees, Myrddin; Adam, Rene; et al. (HPB, 2011)
Background - A standardized definition of post-hepatectomy haemorrhage (PHH) has not yet been established. - Methods - An international study group of hepatobiliary surgeons from high-volume centres was convened and a definition of PHH was developed together with a grading of severity considering the impact on patients' clinical management. - Results - The definition of PHH varies strongly within the hepatic surgery literature. PHH is defined as a drop in haemoglobin level >3g/dl post-operatively compared with the post-operative baseline level and/or any post-operative transfusion of packed red blood cells (PRBC) for a falling haemoglobin and/or the need for radiological intervention (such as embolization) and/or re-laparotomy to stop bleeding. Evidence of intra-abdominal bleeding should be obtained by imaging or blood loss via the abdominal drains if present. Transfusion of up to two units of PRBC is considered as being Grade A PHH. Grade B PHH requires transfusion of more than two units of PRBC, whereas the need for invasive re-intervention such as embolization and/ or re-laparotomy defines Grade C PHH. - Conclusion - The proposed definition and grading of severity of PHH enables valid comparisons of results from different studies. It is easily applicable in clinical routine and should be applied in future trials to standardize reporting of complications. A proposed international definition and grading of severity of post hepatectomy haemorrhage which may enable better comparison of outcomes from future published studies